2015
DOI: 10.1016/j.anbehav.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on social attention in free-ranging rhesus macaques

Abstract: An ethological approach to attention predicts that organisms orient preferentially to valuable sources of information in the environment. For many gregarious species, orienting to other individuals provides valuable social information but competes with food acquisition, water consumption and predator avoidance. Individual variation in vigilance behaviour in humans spans a continuum from inattentive to pathological levels of interest in others. To assess the comparative biology of this behavioural variation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 106 publications
(163 reference statements)
3
34
0
Order By: Relevance
“…Vigilance decreases with increasing neighbors Busia et al (2016), Cowlishaw (1998), Gaynor & Cords (2012) i , Rose & Fedigan (1995), Stojan-Dolar & Heymann (2010), Teichroeb & Sicotte (2012) Vigilance lower with at least one adult neighbor Steenbeek et al (1999), Stojan-Dolar & Heymann (2010), Treves (1998), Treves et al (2001), van Schaik & van Noordwijk (1989 Vigilance increases with increasing neighbors Kutsukake (2006Kutsukake ( , 2007 No significant effect Kutsukake (2006), Watson et al (2015) Distance to neighbors Vigilance increased as distance to nearest group member decreased Suzuki & Sigiura (2011) Vigilance increased as distance to nearest conspecific or heterospecific neighbor increased Robinson (1981), Stojan-Dolar & Heymann (2010) Vigilance higher with few neighbors near and many neighbors farther away, and vice versa.…”
Section: Number Of Neighborsmentioning
confidence: 97%
See 4 more Smart Citations
“…Vigilance decreases with increasing neighbors Busia et al (2016), Cowlishaw (1998), Gaynor & Cords (2012) i , Rose & Fedigan (1995), Stojan-Dolar & Heymann (2010), Teichroeb & Sicotte (2012) Vigilance lower with at least one adult neighbor Steenbeek et al (1999), Stojan-Dolar & Heymann (2010), Treves (1998), Treves et al (2001), van Schaik & van Noordwijk (1989 Vigilance increases with increasing neighbors Kutsukake (2006Kutsukake ( , 2007 No significant effect Kutsukake (2006), Watson et al (2015) Distance to neighbors Vigilance increased as distance to nearest group member decreased Suzuki & Sigiura (2011) Vigilance increased as distance to nearest conspecific or heterospecific neighbor increased Robinson (1981), Stojan-Dolar & Heymann (2010) Vigilance higher with few neighbors near and many neighbors farther away, and vice versa.…”
Section: Number Of Neighborsmentioning
confidence: 97%
“…Mothers with dependent infants more vigilant than those with independent young or females without infants Boinski et al (2003), Treves (1999c), Treves et al (2003) No difference found between adult females with or without infants Treves (1998) All adult individuals increased vigilance after birth of infants Treves et al (2001) Vigilance increased when infant-carrying Steenbeek et al (1999), Stojan-Dolar & Heymann (2010) Age Vigilance increases with age in both sexes Boinski et al (2003), Busia et al (2016), de Ruiter (1986, Fragaszy (1990), Gosselin-Ildari & Koenig (2012) Vigilance decreased with age in both sexes Watson et al (2015) No age-related effects Caine & Marra (1988) Activity Vigilance higher during resting and traveling van Schaik & van Noordwijk (1989) Vigilance higher during resting Cowlishaw (1998), Gaynor & Cords (2012), Stojan-Dolar & Heymann (2010), Suzuki & Sigiura (2011) Vigilance lower during grooming than resting or feeding Cords (1995) Routine vigilance higher during feeding Teichroeb & Sicotte (2012) No difference between feeding or resting Macintosh & Sicotte (2009), Teichroeb & Sicotte (2012 Vigilance higher during foraging than resting Kutsukake (2006) Isbell & Young (1993), Kazahari & Agetsuma (2010) f , Hill & Cowlishaw (2002) h Subgroup size Vigilance lower with larger subgroup sizes but only in boundary areas Busia et al (2016) No effect of daily party size Kutsukake (2006) Group composition…”
Section: A R Ia Ti On I N P Ri M a Te V I Gi La N Ce S T U Di E Smentioning
confidence: 98%
See 3 more Smart Citations